Large‐scale plasma proteomic profiling identifies a high‐performance biomarker panel for Alzheimer's disease screening and staging. Issue 1 (25th May 2021) - Jiang, Yuanbing; Zhou, Xiaopu; Ip, Fanny C.; Chan, Philip; Chen, Yu; Lai, Nicole C.H.; Cheung, Kit; Lo, Ronnie M.N.; Tong, Estella P.S.; Wong, Bonnie W.Y.; Chan, Andrew L.T.; Mok, Vincent C.T.; et al.
Abstract: Introduction: Blood proteins are emerging as candidate biomarkers for Alzheimer's disease (AD). We systematically profiled the plasma proteome to identify novel AD blood biomarkers and develop a high‐performance, blood‐based test for AD. Methods: We quantified 1160 plasma proteins in a Hong Kong Chinese cohort by high‐throughput proximity extension assay and validated the results in an independent cohort. In subgroup analyses, plasma biomarkers for amyloid, tau, phosphorylated tau, and neurodegeneration were used as endophenotypes of AD. Results: We identified 429 proteins that were dysregulated in AD plasma. We selected 19 "hub proteins" representative of the AD plasma protein profile, which formed the basis of a scoring system that accurately classified clinical AD (area under the curve = 0.9690–0.9816) and associated endophenotypes. Moreover, specific hub proteins exhibit disease stage‐dependent dysregulation, which can delineate AD stages. Discussion: This study comprehensively profiled the AD plasma proteome and serves as a foundation for a high‐performance, blood‐based test for clinical AD screening and staging.